Injury and illness surveillance in sports: how golf, tennis, cycling and parasport extended the IOC consensus statement to tailor injury and illness surveillance to specific sports - Dvorak, J.; Pluim, B. (British Journal of Sports Medicine, 2021)
For a sport to develop a meaningful injury prevention strategy, sound epidemiological data are crucial. This, in turn, needs to be based on the analysis of known risk factors involved in the sport so that mitigation strat-egies can be introduced by modifying the rules and laws if necessary. The key objective for medical advisors in sports is to reduce morbidity and to promote the sport as a health-enhancing leisure activity. In this editorial, we aimed to motivate other inter-national sport federations to take similar action. Insufficient physical activity greatly increases the risk of non-communicable diseases, and physical inactivity is one of the biggest public health threats of the 21st century. With a standardised reporting system, as outlined by the IOC in its 2020 Consensus Statement, researchers will now be able to analyse the incidence and prevalence of injuries and make valid comparisons among sports. The sport-specific extensions of the IOC consensus statement may also serve as examples for other international sports federations. This helps to harmonize the surveillance of injury and illness across sports and it will promote the health-enhancingaspects of physical activity.